Teaching artfully - Parker, Meghan (Clover Press, 2021)
"Teaching Artfully draws the reader in as it presents the growth and explorations of an early-career art teacher, the author Meghan Parker. Parker comes to understand both her teaching and art-making practices through making insightful comics. The reader, too will find themselves illuminated and inspired and entertained! Teaching Artfully looks at daily teaching practices, visual literacy, the teacher's experience, relationships, and engagement with life inside and outside of schools. It uses a unique visual form to emphasize the importance of learning to understand and communicate using images. First created as a Masters thesis in the Faculty of Education at Simon Fraser University, Teaching Artfully playfully and earnestly encourages us to see the arts as a way to connect with one another and find our common humanity. Creative people, educators and the general public are sure to connect with the call for meaningful engagement with the arts. Graphic novel lovers of all sorts will find an awakening in Parker's approach to the creation of space and opportunities for students to imagine and create new possibilities. Teaching Artfully is sure to be the most talked about book of the year! "--Provided by publisher.